The tragic Trans-structuring of Myth - Moutsopoulos, Evanghélos (1997)
This paper intends to show how a mythis overcome by the tragic poet by tumingit into a completely new tragedy. In this sense, more than of a re-structuring-simple process of reorganization of the elements of a myth in arder to adaptit to new conditions-, it will be spoken of a trans-structuring, that is, of a total and delibera te overcoming of the former model and of an original articulation of the initial elements complemented by new ones. The tragic trans-structuringof the myth depends on the tragic poet's intention of overcoming the initial mythical structure and offering, thus, a new and autonomous model of the structure of behaviour.